Effects of privacy concerns on older adults’ discontinuous usage intention: the chain mediating effect of technology anxiety and the moderating role of perceived price value - An, Jing; Wan, Kexin; Xiang, Ziyue; Zhu, Xuanyu; An, Jinlong; Yang, Yujie (Frontiers in Public Health, 2025)
IntroductionWith the continuous progress of global information and communication technology, online medical care has become a hot topic. And online health consultation platforms have also emerged and provided patients, especially the older adults, with a new way to obtain health information.ObjectiveTo explore the impact of privacy concerns, technology anxiety, dissatisfaction, and perceived price value on older adults’ discontinuous usage intention of online health consultation platforms.MethodsUsing quantitative analysis method, 254 valid questionnaires were collected online with the sample of older adults aged over 50 years in China. Descriptive statistics and structural equation models were established, and hypothesis testing was carried out using SPSS software.ResultsIn this study, privacy concerns (β = 0.268, p < 0.001), technology anxiety (β = 0.256, p < 0.001), and dissatisfaction (β = 0.433, p < 0.001) directly affect the discontinuous usage intention of online health consultation platforms, among which technology anxiety and dissatisfaction play a mediating role (p < 0.01). Price value moderates the impact of privacy concerns on discontinuous usage intention. The results of this study indicate that the mental state of older adults using the online health consultation platform will significantly affect their dissatisfaction and discontinuous usage intention of the platform.